The Influence of Interpersonal Communication and Service Quality of Cardiologists on Patient Loyalty at Welas Asih Regional General Hospital - Citra Citra (Journal of Social Research, 2025)
Communication in health services has an important role in building patient trust and loyalty to hospitals. Cardiac Services as a leading service at the Welas Asih Hospital in West Java Province recorded 9,177 visits to BPJS patients in 2024. The high number of visits with limited practice time causes interaction between doctors and patients to be limited, potentially causing dissatisfaction, especially in the aspect of communication. This study uses a quantitative descriptive analytical approach with the population of all BPJS outpatients who receive the services of cardiologists. The research sample of 106 respondents was obtained through accidental sampling techniques. Data were collected using questionnaires that had been tested for validity and reliability, then analyzed using multiple linear regression with the help of SPSS. The results showed that physician interpersonal communication (r = 0.751; p < 0.001) and service quality of cardiologists (r = 0.828; p < 0.001) had a positive and significant relationship with patient loyalty. Both variables explain the 69.8% variation in patient loyalty (R² = 0.698). Service quality was the most dominant variable that affected loyalty (? = 0.663; p < 0.001), while interpersonal communication had a smaller effect (? = 0.198; p = 0.043). This research confirms that good service quality and empathetic and clear communication of doctors can increase patient loyalty. Therefore, improving doctors' communication competence and strengthening service excellence in cardiac specialist services is very important to maintain patient trust and loyalty.